La masonería española en Marruecos: Un proyecto colonial (1881-1936) - Aguiar Bobet, Valeria (2020)
The researcher Valeria Aguiar Bobet has defended a doctoral thesis in History, whose title is "La masonería española en Marruecos: un proyecto colonial (1881-1936)" at the Jaume I University in Spain, under the direction of José Antonio Piqueras Arenas and Manuel by Paz Sánchez. The defense was on January 8, 2020.